PENINGKATAN KEMAMPUAN MENULIS SISWA PEMULA MENGGUNAKAN METODE STRUKTUR ANALITIK SINTETIK (SAS) PADA PEMBELAJARAN BAHASA INDONESIA TINGKAT SEKOLAH DASAR (SD) DI KABUPATEN PESISIR BARAT - Elrita, Sherly (STIT AL MULTAZAM, 2020)
The purpose of this study was to improve the writing skills of novice students through the Synthetic Analytical Structures (SAS) method in Indonesian learning at the Elementary School (SD) level. The research method used is the class action method that adapts the design of Kemmis and Taggart which is carried out in two cycles with quantitative and qualitative approaches. The instruments used were the teacher and student activity observation sheets, field notes, and documentation. This research was conducted at SD Negeri 87 Krui, Pesisir Barat Regency when the research was carried out for 2 months in 2020. The results showed that the application of the Synthetic Analytical Structures (SAS) method can improve the writing skills of novice students at the elementary level in the research location. This is indicated by the writing ability of beginner students in each cycle has increased.